2017
DOI: 10.1111/maps.12827
|View full text |Cite
|
Sign up to set email alerts
|

Secondary‐volatiles linked metallic iron in eucrites: The dual‐origin metals of Camel Donga

Abstract: The unique occurrence of abundant (~1 vol%) near‐pure‐Fe metal in the Camel Donga eucrite is more complicated than previously believed. In addition to that component of groundmass metal, scattered within the meteorite are discrete nodules of much higher kamacite abundance. We have studied the petrology and composition of two of these nodules in the form of samples we call CD2 and CD3. The nodules are ovoids 11 (CD2) to 15 (CD3) mm across, with metal, or inferred preweathering metal, abundances of 12–17 vol% (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
(278 reference statements)
0
4
0
Order By: Relevance
“…Non-polymict eucrites typically contain ≤0.3 vol% metal (Delaney et al 1984), which is usually in grains of a few to a few tens of microns in size; most metal grains contain ≤1 wt% Ni (Duke 1965;Mayne et al 2009;this study). Exceptional basaltic eucrite Camel Donga contains about 1 vol% metal containing up to ~0.6 wt% Ni (Cleverly et al 1986;Palme et al 1988;Warren et al 2017). EET 92023 contains ~0.5 wt% metal that is up to ~300 µm across (Kaneda and Warren 1998) and forms composite grains of kamacite, taenite, and probable tetrataenite (Mayne et al 2009;Yamaguchi et al 2017;this study).…”
Section: Cumulate Gabbrosmentioning
confidence: 97%
“…Non-polymict eucrites typically contain ≤0.3 vol% metal (Delaney et al 1984), which is usually in grains of a few to a few tens of microns in size; most metal grains contain ≤1 wt% Ni (Duke 1965;Mayne et al 2009;this study). Exceptional basaltic eucrite Camel Donga contains about 1 vol% metal containing up to ~0.6 wt% Ni (Cleverly et al 1986;Palme et al 1988;Warren et al 2017). EET 92023 contains ~0.5 wt% metal that is up to ~300 µm across (Kaneda and Warren 1998) and forms composite grains of kamacite, taenite, and probable tetrataenite (Mayne et al 2009;Yamaguchi et al 2017;this study).…”
Section: Cumulate Gabbrosmentioning
confidence: 97%
“…2013, 2017; Warren et al. 2014, 2017; Pang et al. 2017; Patzer and McSween 2018; Roszjar 2019; Vollmer et al.…”
Section: Introductionmentioning
confidence: 99%
“…2013; Roszjar 2019); (3) secondary Fe metal, in, e.g., Camel Donga and NWA 5738 (Warren et al. 2014, 2017); and (4) Fe‐enrichments and/or veinlet‐like textures mainly composed of fayalitic olivine in, e.g., Pasamonte, NWA 049/1000/1109/2061/5073/5738, Yamato (Y)‐75011/82202 basaltic eucrites (Takeda et al. 1983, 1994; Warren 2002; Barrat et al.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PO tridymite is present in the clast A, and MC tridymite was in the clast B, indicating that each clast has experienced distinct cooling rates before brecciation. These supported that Camel Donga should be classified as a polymict eucrite as Warren et al (2017) suggested by pyroxene composition and Fe-nodule, while there is a possibility that the clasts in Camel Donga reflect a large variety of the cooling rate in the same mass. Therefore, silica minerals can distinguish whether brecciated eucrites are monomict or polymict by combining with pyroxene chemical compositions.…”
Section: Other Possible Indications By Silica Mineralsmentioning
confidence: 61%